FORMULATION DEVELOPMENT AND IN VITRO CHARACTERIZATION OF TERNARY HYDROTROPIC SOLID DISPERSIONS OF ACECLOFENAC - SARKAR, PRASENJIT; BISWAS MAJEE, SUTAPA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Among the various strategies employed to enhance solubility, dissolution, and bioavailability of poorly soluble drugs in vivo, formulation of solid dispersion (SD) using hydrophilic and/or water-soluble carriers with varying physicochemical characteristics seems to be a developable, economically viable and easy option. The goal of the present study was to explore the possibilities of skimmed milk (SKM)-urea (U)-crospovidone (CP) as a novel ternary mixture of carrier-hydrotrope-superdisintegrant in SD of poorly water-soluble aceclofenac (ACF). Methods: Compatibility of ACF and ternary mixture of SKM-U-CP was confirmed by FTIR spectroscopic analysis. SDs of ACF-SKM, ACF-SKM-U and ternary hydrotropic SD, and ACF-SKM-U-CP were prepared in varying ratios of 1:1–1: 5 for ACF-SKM; 1:5:0.5, 1:5:0.75, and 1:5:1 for ACF-SKM-U and 1:5:0.75:0.25–1:5:0.75:1 for ACF-SKM-U-CP by solvent evaporation technique and were characterized by their solubility enhancement (compared to pure drug) at 25°C and drug dissolution profiles in double-distilled water and phosphate buffer (pH 6.8). Results: Based on solubility enhancement data (82.10% and 44.06%) and maximum cumulative percentage drug release data (88.45% in 9 min and 76.18% in 60 s) in double-distilled water and phosphate buffer, respectively, ACF-SKM-U(1:5:0.75) was found to the best among ACF-SKM and ACF-SKM-U SDs which were used for studying the effect of adding CP as superdisintigrant. ACF: SKM: U: CP (1: 5: 0.75: 0.50) exhibited maximum solubility enhancement of 83.92% and 49.69% and cumulative percentage release of 98.55 % in 9 min and 85.67 % in 60 s in double-distilled water and buffer, respectively. Conclusion: Therefore, the novel ternary mixture of SKM-U-CP has demonstrated marginal superiority over SKM as carrier for from hydrotropic SDs of ACF.